The Effect of Chemotherapy on Improving The Quality of Life in Patients with Nasopharyngeal Carcinoma - A. Ahmad Khaidir Agussalim; Moh. Reza Zainal Abidin; Khaeruddin HA (The International Journal of Medical Science and Health Research, 2025)
Nasopharyngeal carcinoma is the most common malignant tumor of the head and neck region found in Indonesia. Chemotherapy is a cancer treatment that utilizes drugs to halt the growth of cancer cells. The assessment of quality of life in cancer patients is frequently used as a benchmark for therapeutic success and can be employed to evaluate the long-term cost-effectiveness of therapy. This study aims to analyze the effect of chemotherapy on improving the quality of life of patients with nasopharyngeal carcinoma. The research method involved a literature review of various previous studies that discussed the effect of chemotherapy on improving the quality of life of patients with nasopharyngeal carcinoma. The analysis revealed that the health-related quality of life (HRQOL) of nasopharyngeal cancer patients undergoing chemotherapy varies due to the effects of the cancer itself, the effects of chemotherapy, and the individual's life goals and expectations. This study suggests that nasopharyngeal carcinoma patients undergoing chemotherapy should anticipate the severity of side effects by receiving premedication and ensuring physical and mental preparedness before treatment.